2016
DOI: 10.1016/j.cell.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Control of Phase-Separated Cellular Bodies

Abstract: SUMMARY Cellular bodies such as P bodies and PML nuclear bodies (PML NBs) appear to be phase-separated liquids organized by multivalent interactions among proteins and RNA molecules. Although many components of various cellular bodies are known, general principles that define body composition are lacking. We modeled cellular bodies using several engineered multivalent proteins and RNA. In vitro and in cells, these scaffold molecules form phase-separated liquids that concentrate low valency client proteins. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
1,343
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,101 publications
(1,398 citation statements)
references
References 67 publications
54
1,343
0
1
Order By: Relevance
“…Multivalent interactions driven by IDRs can reduce solubility and facilitate body formation, with the strong interactions governing polymerization and the weak interactions governing solubility. 86 Interestingly, conversion over time of phase separated droplets composed of IDRs and RNAs from a liquid like to a more fiber like state has been demonstrated in vitro suggesting that IDRs may contribute to the "maturing" of the HLB in response to transcriptional activation as described above. 90,91 Post-translational modifications may also modulate phase separation associated with gene expression.…”
Section: Does Phase Separation Help Drive Hlb Assembly?mentioning
confidence: 99%
See 1 more Smart Citation
“…Multivalent interactions driven by IDRs can reduce solubility and facilitate body formation, with the strong interactions governing polymerization and the weak interactions governing solubility. 86 Interestingly, conversion over time of phase separated droplets composed of IDRs and RNAs from a liquid like to a more fiber like state has been demonstrated in vitro suggesting that IDRs may contribute to the "maturing" of the HLB in response to transcriptional activation as described above. 90,91 Post-translational modifications may also modulate phase separation associated with gene expression.…”
Section: Does Phase Separation Help Drive Hlb Assembly?mentioning
confidence: 99%
“…68,[85][86][87] In this process the physical chemical properties of body components promote a phase transition when the concentration of the component(s) exceeds their solubility limit, such as when molecules precipitate out of solution and form a crystal. The phase transition need not result in a solid structure: Many bodies display liquid like properties, similar to a lipid droplet within an aqueous environment.…”
Section: Does Phase Separation Help Drive Hlb Assembly?mentioning
confidence: 99%
“…Several groups have shown that multivalent proteins enriched with highly disordered domains are capable of forming liquid droplets in vitro that display many characteristic features of NBs, including fusion and fission events. 86,87,90,91,145 It has also been suggested that separation of nucleoli, paraspeckles 146 and Nuage bodies formed by DEAD-box helicase 4 (Ddx4) protein 86,147 is driven by these disordered domains-containing proteins. Coilin and its homologs are highly disordered but Arabidopsis thaliana-derived coilin is stabilized upon snRNA binding leading to multimerization in vitro, 114 which can be assumed to contribute to CB nucleation.…”
Section: Proteinmentioning
confidence: 99%
“…8,[103][104][105] It has been established that the assembly and structural maintenance of NBs is predominantly influenced by several prominent architectural proteins that are able to self-associate to form homo-and hetero-oligomers. 80,87 Many CB proteins have been identified as structurally essential for CB integrity, but little is known about the biochemical properties and regulation of each factor. The majority of our knowledge regarding the proteins essential for CB assembly regards coilin and SMN, which are the classical CB marker proteins, as well as a limited number of other proteins.…”
Section: Pulling Itself Together: Oligomerization and Cajal Body Assementioning
confidence: 99%
See 1 more Smart Citation